The Politics of the American Knowledge Economy. Issue 1 (April 2022) - Short, Nicholas
Abstract: The American knowledge economy (AKE) is not a foreordained transition in the organization of economic production, nor is it a form of political economy shaped predominately by the political demands of highly educated workers. It is a politically generated consensus for producing economic prosperity and economic advantage over other nations in which intellectual property (IP), and the businesses that produce it, play a leading role. The history of AKE development reveals as much. In the AKE's formative period, from 1980 to 1994, IP producers and a faction of neoliberal Democrats (the "Atari Democrats"), not decisive middle-class voters, played a pivotal role in reconfiguring institutions of American political economy to hasten the AKE transition. Their vision of AKE development inherently complicated the Democratic Party's attitude toward rising market power and continues to shape contemporary disputes within the party over antitrust enforcement and the validity of the AKE project itself.